PHYSICOCHEMICAL CHARACTERIZATION OF PEDADA FRUIT (Sonneratia caseolaris) SLICE JAM WITH THE ADDITION OF CARAGEENAN - Fairuzalfa, Najma Fadila; Rochma, Shinta Ainur; Andriyono, Sapto; Saputra, Eka (Universitas Mataram, 2025)
This study aims to evaluate the effect of carrageenan addition on the physicochemical properties of fruit slice jam made from Sonneratia caseolaris. This mangrove fruit contains 0.32% pectin, making it a potential raw material for jam production. However, conventional jam has limitations in practicality, leading to the development of fruit slice jam, which has a compact, non-sticky, and plastic-like texture. The study employed a Completely Randomized Design (CRD) with four treatments: P0 (control, 2% pectin), P1 (1.25% carrageenan), P2 (1.50% carrageenan), and P3 (1.75% carrageenan), each replicated five times. The physical parameters analyzed included hardness, cohesiveness, adhesiveness, and springiness, while the chemical parameters consisted of moisture content, ash content, reducing sugar, and pH. Data were analyzed using one-way ANOVA at a 95% confidence level, followed by Duncan's Multiple Range Test (DMRT). The results indicated that increasing carrageenan concentration significantly (P<0.05) decreased adhesiveness, springiness, and moisture content, while hardness, cohesiveness, ash content, reducing sugar, and pH increased. Thus, carrageenan addition significantly influences the physicochemical properties of fruit slice jam made from S. caseolaris, offering a promising innovation for fruit-based jam products